1996
DOI: 10.1103/physrevb.54.2101
|View full text |Cite
|
Sign up to set email alerts
|

Reaction ofI2with the (001) surfaces of GaAs, InAs, and InSb. I. Chemical interaction with the substrate

Abstract: InAs͑001͒-c͑8ϫ2͒, InSb͑001͒-c͑8ϫ2͒, and several reconstructions of GaAs͑001͒ are exposed at room temperature to iodine molecules ͑I 2 ͒. Low-energy electron diffraction ͑LEED͒ and synchrotron soft x-ray photoelectron spectroscopy ͑SXPS͒ are employed to study the surfaces as a function of I 2 dose and sample anneal. In the exposure range studied, GaAs and InAs become saturated with I 2 , resulting in removal of the clean surface reconstruction and the formation of a very strong 1ϫ1 LEED pattern. Iodine bonds pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 45 publications
1
34
0
Order By: Relevance
“…Examples of the morphologies that result from etching GaAs with Br 2 under various conditions are shown in Figure 2. Varekamp et al (93) observed similar etchinduced morphologies, i.e. rectangular etch pits and jagged step edges, in the room-temperature reaction of InSb(001) with I 2 .…”
Section: Geometric Structurementioning
confidence: 79%
See 4 more Smart Citations
“…Examples of the morphologies that result from etching GaAs with Br 2 under various conditions are shown in Figure 2. Varekamp et al (93) observed similar etchinduced morphologies, i.e. rectangular etch pits and jagged step edges, in the room-temperature reaction of InSb(001) with I 2 .…”
Section: Geometric Structurementioning
confidence: 79%
“…At other times, however, Cl 2 adsorption leads to the complete removal of the low-energy electron diffraction (LEED) pattern, thereby indicating that the surface has become disordered. This has been seen for Cl 2 (93) describe in detail the coverage dependence of the LEED pattern for I 2 adsorption on GaAs(001)-4 × 6, which is representative of I 2 adsorption on several other surfaces. Small I 2 exposures simply increase the background intensity without changing the 4 × 6 pattern, suggesting that the iodine initially adsorbs randomly on the surface.…”
Section: Geometric Structurementioning
confidence: 94%
See 3 more Smart Citations